Application of Technology in University Library and Users’ Satisfaction: A Case of Pokhara University, Nepal - Dallakoti, Min Kumari (Access: An International Journal of Nepal Library Association, 2025)
Introduction of technology in university libraries is essential since there is substantial number of users seeking the library services in minimum time within a short period of high quality and dedication. Prior to establishing the technology, all activities were performed manually, which was time consuming and less accurate. The study aims to examine the impact of technology on the users of central library of Pokhara University. The study was conducted among the conveniently selected three hundred respondents including students, research scholars, and faculty members. A structured questionnaire using a five-point Likert scale was used to collect the primary data. Both descriptive and inferential tools have been used to analyses the results. Out of twenty constructs, the mean value of nine constructs is average and more (3.0) eleven constructs are less than average. Training is most sought (4.08) while productivity of the staff is least sought (2.81). These constructs were categorized under five dimensions viz. Ease of Access and Usability, Technological Infrastructure, Resource Availability, Support and Assistance, and Impact on Learning and Research. Majority of respondents are expecting services at the library during the off-office hours and holidays. The findings reveal that impact of RFID system is found significant based on the respondents' sex (p=0.001) while not significant based on age (p=0.627), education (p=0.705), and different faculties (p=0.862). Learning and research are more influenced by technological infrastructure and support and assistance followed by resource availability and ease of access and usability. University authorities suggested paying more attention to technological advancement, providing more training and orientation to improve the service quality of library.